EFEK GOOD CORPORATE GOVERNANCE TERHADAP GREEN ECONOMY DI PERUSAHAAN PERTAMBANGAN INDONESIA - Bimo Wahyu Adi; Dul Muid (Diponegoro Journal of Accounting, 2025)
In recent years, the issue about Green Economy has been widely discussed. Green Economy becoming mainstream in global economic dynamics and a lot of country are moving towards Green Economy. Companies also have another goal, namely meeting stakeholder needs. In order to realize these two goals, companies implement Good Corporate Governance (GCG) to keep them running smoothly. So, the question arises whether Good Corporate Governance can affect Green Economy in the area. This research uses annual report dan sustainability report from 18 Indonesian mining companies in 2021-2023 period. This research aims to test the relationship between Good Corporate Governance through managerial ownership and board of commissioners with Green Economy. Descriptive data analysis method used to measure managerial ownership and board of commissioners, then interactive model data analysis used to measure the component from Green Economy namely greenhouse gas emissions, tree planting, and waste processing. F-test data analysis used to test the direct relevancy between managerial ownership and board of commissioners to Green Economy. The results of this study show that managerial ownership do not have significant influence towards Green Economy. So as board of commissioners that do not have significant influence towards Green Economy. This conclusion is inversely proportional with the initial hypothesis of this study.